2017
DOI: 10.1055/s-0043-103964
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human Acidic Fibroblast Growth Factor (aFGF) Expressed in Nicotiana benthamiana Potentially Inhibits Skin Photoaging

Abstract: Responding to the need for recombinant acidic fibroblast growth factor in the pharmaceutical and cosmetic industries, we established a scalable expression system for recombinant human aFGF using transient and a DNA replicon vector expression in . Recombinant human-acidic fibroblast growth factor was recovered following infiltration of . The optimal time point at which to harvest recombinant human acidic fibroblast growth factor expressing leaves was found to be 4 days post-infiltration, before necrosis was evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…These results were also supported by histomorphometric analysis of irradiated 3D skin explants, where high levels of proliferating cells along with decreased apoptotic signal was observed in response to ATS treatment. This effect may be attributable to the strong mitogenic response shown by dermal cells after treatment with specific growth factors such as EGF and FGF even in the presence of UV radiation [33, 35]. In fact, after 3 days from the treatment, ATS showed to promote the proliferative activity of dermal fibroblasts up to 2.3-fold compared with irradiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results were also supported by histomorphometric analysis of irradiated 3D skin explants, where high levels of proliferating cells along with decreased apoptotic signal was observed in response to ATS treatment. This effect may be attributable to the strong mitogenic response shown by dermal cells after treatment with specific growth factors such as EGF and FGF even in the presence of UV radiation [33, 35]. In fact, after 3 days from the treatment, ATS showed to promote the proliferative activity of dermal fibroblasts up to 2.3-fold compared with irradiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…Ha et al . (2017) interestingly showed that the expressed level of the human acidic fibroblast growth factor (aFGF) decreased approximately two-fold lower in the presence of P19 silencing inhibitor 32 . This result is in accordance with our antithetical results that the decrease of the expression level has been five-fold lower in N .…”
Section: Dicussionmentioning
confidence: 99%
“…On the contrary, there are some reports that P19 does not affect the expression 30 or decreases the amount of the expression in N . benthamiana 31 , 32 . Therefore, implementing the P19 protein should be examined for each recombinant protein and cultivar independently.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, epidermal GF (EGF), vascular endothelial GF (VEGF), keratinocyte GF (KGF), insulin-like GF (IGF), and broblast GF (FGF) family members are used for wound healing, curing and targeting diseases, and stimulating hair growth [3][4][5][6][7][8][9][10]. Currently, because their roles in cellular regulation in vivo include anti-wrinkle, anti-aging, anti-hair loss, and tissue repair effects, GFs are also used as cosmetic additives [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…With an increasing interest in functional cosmetics, the demand for GFs has also increased. Various expression systems, including Escherichia coli [1,[15][16][17][18][19], Bacillus subtilis [20], mammalian cell [21], baculovirus [22], silkworm [23,24], and plant [11,12] systems, are used for cost-effective and e cient production of recombinant GFs. Among them, the E. coli system is frequently used for the production of recombinant proteins because of facile genetic modi cation, rapid protein expression, and high growth rate.…”
Section: Introductionmentioning
confidence: 99%